1987
DOI: 10.2307/1939199
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Patterns of Ecosystem Processes and Community Structure in a Subarctic River Continuum

Abstract: Ecosystem processes and community structure in running waters of the boreal forests of Quebec, Canada, are strongly influenced by climate and channel geomorphology. Here we present an overview of a project examining longitudinal trends as small streams gradually coalesce into large rivers, summarizing our results in a series of budgets and predictive equations describing changes in organic carbon dynamics and community structure. There were significant trends with stream order for 70% of the 73 components, pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
201
1
2

Year Published

1996
1996
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 283 publications
(212 citation statements)
references
References 35 publications
8
201
1
2
Order By: Relevance
“…Kuehne (1962) studied the relationship between fish distribution and stream order; this correlation that has been frequently used when analyzing the longitudinal distribution of fish. Normally, the relationship between fish distribution and stream order is well matched with longitudinal fish distribution (Naiman et al, 1987;Beecher et al, 1988;Paller, 1994;Jang et al, 2008), although exceptions have been reported (Hughes and Gammon, 1987;Omernik, 1981, 1983). Although altitude alone can effectively predict fish distribution, a combination of altitude and stream order is more effective in this respect.…”
Section: Discussionmentioning
confidence: 86%
“…Kuehne (1962) studied the relationship between fish distribution and stream order; this correlation that has been frequently used when analyzing the longitudinal distribution of fish. Normally, the relationship between fish distribution and stream order is well matched with longitudinal fish distribution (Naiman et al, 1987;Beecher et al, 1988;Paller, 1994;Jang et al, 2008), although exceptions have been reported (Hughes and Gammon, 1987;Omernik, 1981, 1983). Although altitude alone can effectively predict fish distribution, a combination of altitude and stream order is more effective in this respect.…”
Section: Discussionmentioning
confidence: 86%
“…Many other studies have tried to explain the macroinvertebrate patterns along the longitudinal section of rivers Winterbourn et al, 1981;Culp & Davies, 1982;Cushing et al, 1983;Statzner & Higler, 1985;Naiman et al, 1987;Brussock & Brown, 1991;Palmer et al, 1994). To explain the observed faunal gradient along the rivers in these studies, two different views have emerged.…”
Section: Introductionmentioning
confidence: 99%
“…Headwaters contribute significantly to CO 2 outgassing via microbial activity 3 , which partly reflects the geomorphic complexity of low-order streams created by spatial variations of hydraulics and substrate 4 . In temperate environments and higher latitudes, headwater rivers can also store disproportionate amounts of carbon in coarse dead wood relative to downstream portions of river networks 5 . The rate at which organic matter is delivered to headwater rivers, and the conditions that facilitate either storage or downstream export of this organic matter, thus exert important influences on watershed-scale carbon fluxes.…”
mentioning
confidence: 99%